Towards responsible production, consumption and food security in China: A review of the role of novel alternatives to meat protein - Ying Zhu; Toritseju Begho (Future Foods, 2022)
Rapid economic growth and urbanization are driving a growing and changing demand for food in China. However, food production has contributed significantly to greenhouse gas (GHG) and human-induced nitrogen emissions. Specifically, beef and pork are two major contributors to China's direct GHG footprint from livestock. The shift from conventional meat to meat protein alternatives is reportedly one of the promising strategies to reduce resource use and emissions. The paper reviews the literature on whether novel meat alternatives can contribute to the attainment of sustainable development goal 2 (SDG 2), whether meat alternatives have a lower ecological footprint, and whether its supply is sustainable – a step toward achieving SDG 12. We observed that most studies portrayed the environmental footprint of meat alternatives in favourable terms, with few dissenting opinions. In addition, meat alternatives have been shown to expand the supply of protein, possess attributes that are important for food stability and can increase the availability of protein-rich foods to meet the nutritional needs of people. However, there are safety concerns and negative perceptions among the public. The insights from this study will be useful in assessing the prospects and informing decisions in moving towards responsible production, consumption and food security in China.